ANALISIS USAHA TANI DAN TINGKAT ADOPSI TEKNOLOGI PENGENDALIAN PENYAKIT CVPD (Kasus di Desa Tebas Sungai, Kecamatan Tebas, Sambas, Kalimantan Barat) ANALYSIS OF FARMING AND LEVEL OF TECHNOLOGY ADOPTION OF CVPD DESEASE CONTROL (Case in Tebas Sungai Vill - Rusli Burhansyah (Agros Journal of Agriculture Science, 2014)
Penyakit CVPD pada tanaman jeruk Siam di Sambas cukup mengkhawatirkan. Ketidakseriusan penanganan penyakit ini akibat tidak efektifnya sistem penyuluhan. Tujuan: mengetahui kelayakan usaha tani dan tingkat adopsi teknologi pengendalian CVPD di Sambas. Metode: pendekatan survei. Waktu: Mei dan Juni 2012. Dilaksanakan di desa Tebas Sungai, Kecamatan Tebas. Data primer diperoleh dari petani dengan wawancara. Data sekunder dari Dinas di Sambas. Penentuan responden menggunakan Proportionate Statified Random Sampling sebanyak 38 orang.  Hasil: budidaya jeruk layak dikembangkan (R/C >1).  Keuntungan selama setahun  Rp 14.143.340. Tingkat adopsi petani demplot cukup baik, dibandingkan dengan petani non demplot dan diluar kecamatan Tebas (Kecamatan Semparuk). Sebagian besar petani (66,67 persen) tingkat adopsi cukup baik, dan sisanya 33,33persen belum mengadopsi teknologi pengendalian CVPD. Komponen teknologi CVPD yang perlu mendapat perhatian adalah pengendalian penyakit diplodia dan panen tepat waktuCVPD in citrus Siam Pontianak in Sambas district quite alarming. On the other hand, the conditions of handling the lack of seriousness of this disease due to the ineffectiveness of the extension system in Sambas district. Necessary efforts to control the disease this CVPD. The purpose of this study was to determine the feasibility of farming and the level of technology adoption CVPD disease control in Sambas district. The research method used survey approach. When the study in May and June 2012. The research was conducted in the village of Tebas Sungai, Tebas Sub distric.. Primary data were collected from farmers. Secondary data were obtained Department / Agency Sambas district. The primary data obtained through interviews using questionnaires. The method to determine respondents using statified Proportionate Random Sampling technique. With the number of farmers 38 people. From the analysis of farming, cultivation of oranges should be developed (R / C> 1). Benefits during the year around USD 14.14334 million, farmer adoption -level pretty good plots, compared with non-farmer plots and sub-districts outside Slash (Subdistrict Semparuk). Most farmers (66.67%) is quite good adoption rate, and the remaining 33.33% is not adopt CVPD control technology. CVPD technology components that need attention are diplodia disease control and timely harvest.